2013
DOI: 10.1002/uog.12487
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable gelatin plug does not prevent iatrogenic preterm premature rupture of membranes after fetoscopic laser surgery for twin–twin transfusion syndrome

Abstract: Objective Despite fetoscopic laser ablation (FLA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…PROM is the most common iatrogenic complication following fetoscopic laser treatment for TTTS [9]. The overall rate of PROM reported in our study (25.9%) is consistent with the range of PROM outcomes reported recently from a single-center series using different fetoscopic instrumentation [16,17,20,21,22,23,24]. Cervical length, and not the fetoscopic technique, was demonstrated in our large multicenter study to be associated with PROM <4 weeks.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…PROM is the most common iatrogenic complication following fetoscopic laser treatment for TTTS [9]. The overall rate of PROM reported in our study (25.9%) is consistent with the range of PROM outcomes reported recently from a single-center series using different fetoscopic instrumentation [16,17,20,21,22,23,24]. Cervical length, and not the fetoscopic technique, was demonstrated in our large multicenter study to be associated with PROM <4 weeks.…”
Section: Discussionsupporting
confidence: 79%
“…Few studies have evaluated the factors associated with PROM and PTB following fetoscopic laser [5,9,13,14,16,17,18,19,20]. No prior study has attempted to compare outcomes against different invasive fetoscopic techniques, which may contribute to complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…His cases were all performed after July 2012. This result compares favorably with that reported by the experienced operators in Moise's group (75%) 8 . Given that our study was not a randomized controlled trial, and that the two techniques were employed sequentially in our study, the question is still valid, and is one that, hopefully, will be answered soon by the randomized controlled trial that is underway.…”
Section: Replysupporting
confidence: 80%
“…The use of a chorioamnion plug has shown promise in animal studies [15,16] and some clinical studies [17], but has not been shown to be universally successful in retrospective human studies [5,18]. Chorioamnion separation has also been shown to increase the rate of iPPROM, from 23 to 74% (relative risk 3.2, 95% CI 1.9-4.4) [19].…”
Section: Discussionmentioning
confidence: 99%